CTP synthetase activity assay by liquid chromatography tandem mass spectrometry in the multiple reaction monitoring mode. (6th January 2020) - Boschat, Anne‐Claire; Minet, Norbert; Martin, Emmanuel; Barouki, Robert; Latour, Sylvain; Sanquer, Sylvia
Abstract: Cytidine 5′‐triphosphate synthetase (CTPS) is known to be a central enzyme in the de novo synthesis of CTP. We have recently demonstrated that a deficiency in CTPS1 is associated with an impaired capacity of activated lymphocytes to proliferate leading to a combined immunodeficiency disease. In order to better document its role in immunomodulation, we developed a method for measuring CTPS activity in human lymphocytes. Using liquid chromatography‐mass spectrometry, we quantified CTPS activity by measuring CTP in cell lysates. A stable isotope analog of CTP served as internal standard. We characterized the kinetic parameters Vmax and Km of CTPS and verified that an inhibition of the enzyme activity was induced after 3‐deazauridine (3DAU) treatment, a known inhibitor of CTPS. We then determined CTPS activity in healthy volunteers, in a family whose child displayed a homozygous mutation in CTPS1 gene and in patients who had developed or not a chronic lung allograft dysfunction (CLAD) after lung transplantation. Linearity of the CTP determination was observed up to 451 μmol/L, with accuracy in the 15% tolerance range. Michaelis‐Menten kinetics for lysates of resting cells were Km =280±310 μmol/L for UTP, Vmax =83±20 pmol/min and, for lysates of activated PBMCs, Km =230±280 μmol/L for UTP, Vmax =379±90 pmol/min. Treatment by 3DAU and homozygous mutation in CTPS1 gene abolished the induction of CTPS activity associated with cell stimulation, and CTPS activity was significantly reduced in the patients who developed CLAD. We conclude that this test is suitable to reveal the involvement of CTPS alteration in immunodeficiency.